2020
DOI: 10.1021/acsanm.9b02520
|View full text |Cite
|
Sign up to set email alerts
|

Carbonized Hybrid Micro/Nanostructured Metasurfaces Produced by Femtosecond Laser Ablation in Organic Solvents for Biomimetic Antireflective Surfaces

Abstract: Hybrid micro/nanostructures and light-absorbing pigment of melanin are two key factors for the excellent antireflective properties of the butterfly wings of Ornithoptera goliath. In this work, femtosecond laser ablation of metals in an organic solvent (FLAMOS) was used to generate hybird micro/ nanostructured cross-linked ultrahigh/low spatial frequency laserinduced periodic surface structures (UHSFLs/LSFLs), which well mimic the antireflective architecture of Ornithoptera goliath. The simultaneously deposited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
74
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(82 citation statements)
references
References 68 publications
5
74
3
Order By: Relevance
“…According to the fact that 780 nm is the period of Ta-LIPSS obtained by fs-LA in air at λ = 1030 nm, the periods of Ta-LIPSSs obtained in water and ethanol/acetone at the wavelength of 1030 nm should be 441 and 421 nm, respectively. This calculation fits well with the period range of 400-600 nm experimentally obtained by fs-LA in water and acetone at a close wavelength of 1045 nm, as presented in this work and our previous work [18]. Hence, it can be concluded that the theoretical trend of Λ ∝ 1/n 2 proposed by Kudryashov et al [48] is at least applicable to some cases.…”
Section: Sem Characterization Of Hierarchical Micro/nanostructure Morsupporting
confidence: 92%
See 4 more Smart Citations
“…According to the fact that 780 nm is the period of Ta-LIPSS obtained by fs-LA in air at λ = 1030 nm, the periods of Ta-LIPSSs obtained in water and ethanol/acetone at the wavelength of 1030 nm should be 441 and 421 nm, respectively. This calculation fits well with the period range of 400-600 nm experimentally obtained by fs-LA in water and acetone at a close wavelength of 1045 nm, as presented in this work and our previous work [18]. Hence, it can be concluded that the theoretical trend of Λ ∝ 1/n 2 proposed by Kudryashov et al [48] is at least applicable to some cases.…”
Section: Sem Characterization Of Hierarchical Micro/nanostructure Morsupporting
confidence: 92%
“…The refractive indices of air, water, ethanol and acetone are 1, To compare the difference between our results and previous reports, LIPSSs obtained on Ta and W by fs-LA in both air and liquids are summarized in Table 1. In our previous report, we showed that, under the same ablation condition, the periods of LIPSSs (including both LSFLs/HSFLs and UHSFLs) obtained by fs-LAL in acetone [18] were almost the same as those produced by fs-LA in water shown in this work. Studies on Ta-LIPSS are very limited.…”
Section: Sem Characterization Of Hierarchical Micro/nanostructure Morsupporting
confidence: 79%
See 3 more Smart Citations